Rapunzel syndrome in adult with mysterious presentation: a rare case report with literature review. (April 2019) - Kumar, Navin; Huda, Farhanul; Gupta, Rohit; Payal, YS; Kumar, Utkarsh; Mallik, Dhiraj
Bezoars are indigestible foreign material in the gastrointestinal tract (GIT). A phytobezoar is a mass of plant material, while a trichobezoar consists of matted hair. This is found most commonly in the stomach in children who chew their long hair. When a gastric trichobezoar extends to the duodenum or jejunum, this is known as Rapunzel syndrome (RS), after a famous Brothers' Grimm fairy tale. Our patient presented with haematemesis, localised peritonitis, a palpable epigastric mass, coagulopathy, severe anaemia and deranged liver function tests. An abdominal computed tomography scan was suggestive of a bezoar; gastroduodenoscopy confirmed the diagnosis. Treatment of trichobezoars normally involve endoscopic removal or gastrotomy and psychiatric intervention. They may also cause haematemesis, gastric outlet obstruction, gastric ulceration and perforation, multiple jejuno-jejunal intussusception, acute pancreatitis and cholestatic jaundice. Trichobezoar was first reported in the 18th century by Baudamant in a 16-year-old boy. RS was first described in 1968.